TINDAK PIDANA KEKERASAN TERHADAP PEREMPUAN (Studi Etiologi Kriminal di Wilayah Hukum Polres Banyumas) - Johny, Ruby Hadiarti (Faculty of Law, Universitas Jenderal Soedirman, 2011)
The violence against women is increasing in number. This article discusses the factors underlying the occurrence and other form of violence against women that occurred in the Police Banyumas region. Sociological juridical approach used in this research. Specification of research is descriptive. The data used are primary and secondary data. The dominant factors that cause criminal violence to women are dominated by economic factors about 70%, cultural factors about 15%, affair factors about 10 %, and lack of communication between family factors about 5 %. The types of criminal violence to women based on data from LSM Lentera Perempuan WCC Banyumas, Victims, and Poice Banyumas region most of the type criminal violence to women is domestic violence, as physic, psychological, sexual violence, and negligence of household. The problem solving is with the litigation process or non litigation process. The litigation process with criminal law process and the non litigation process with mediation. Keywords: Domestic violence, form of violence, cause of violence